The core aspects of mother expressed emotions as a predictor of Vocational identity in Pakistani adolescents: A Structural Equation Modeling Approach - Sumara Masood (NUST Journal of Social Sciences and Humanities)
In mental health ‘Expressed emotion’ used to denote the intensity of emotional expression within the family context. Intensities of expressed emotion might be high or low and might be considered ‘negative or ‘positive. Mother Expressed Emotion’ refers to the range of expressed emotion towards the individuals, (Brown, 1985).1 Adolescents are individuals that are in their next decade of life and face internal struggles or circumstances that might compromise directly their mental health (United Nations, 2017).2 Where the others factors play the role in perception of occupational motivation and abilities, the home climate is main element which put influences on adolescents. The current study aim was to identify and explore the role of mother expressed emotions and its association with vocational identity. To examine this, study was conducted on 500 mothers and 500 their adolescents from 2022 to 2023 academic year, to measure the mother expressed emotions; parental expressed emotions scale (Akhtar & Bano, 2021)3 was used and vocational identity scale was used for adolescents (Holland et al., 1980).4 The data was analyzed with regression analysis and structural equation modeling by using SPSS 27 and AMOS 27. Significant positive prediction was found among mother expressed emotions as positive remarks found 20% and warmth found 45% predictor of vocational identity in adolescents, while emotional-over involvement showed -16% significantly negative predictor of vocational identity among adolescents. It was concluded that proposed theoretical model explained that mother expressed emotions are significant predictor of vocational identity and results founded parallel with the previous researches (Gupta & Leong, 2015).5